1-Trifluoromethoxyphenyl-3-(1-Propionylpiperidin-4-yl) Urea Protects the Blood-Brain Barrier Against Ischemic Injury by Upregulating Tight Junction Protein Expression, Mitigating Apoptosis and Inflammation InVivo and In Vitro Model - Yi, Xingyang; Xu, Chongxi; Huang, Pan; Zhang, Linlei; Qing, Ting; Li, Jie; Wang, Chun; Zeng, Tao; Lu, Jing; Han, Zhao (Frontiers in Pharmacology, 2020)
We previously have revealed that 1-trifluoromethoxyphenyl-3-(1- propionylpiperidin-4-yl) urea (TPPU), as a soluble epoxide hydrolase (sEH) inhibitor can reduce infarct volume, protect blood-brain barrier (BBB) and brain against ischemic injury in rats. Here, we investigated the potential mechanisms of TPPU on BBB integrity in both in permanent middle cerebral artery occlusion (pMCAO) rat model and in oxygen-glucose deprivation/reperfusion (OGD/R)-induced human brain microvascular endothelial cells (HBMVECs) model. In pMCAO rat, TPPU administration decreased brain edema and Evans blue content, increased tight junction proteins (TJs) expression of claudin-5, occludin and zonula occludens-1 (ZO-1). In OGD/R model, OGD/R significantly increased permeability and cell apoptosis, downregulated the expression of claudin-5, ZO-1, occludin, and lymphoma (Bcl)-2. Notably, TPPU pretreatment effectively protected the BBB integrity by reducing the permeability, promoting expression of claudin-5, ZO-1, occluding and Bcl-2, mitigating reactive oxygen species (ROS) injury and release of interleukin-1β (IL-1β), IL-6β and tumour necrosis factor-α (TNF-α), downregulating expression of matrix metalloproteinase-9 (MMP-9), MMP-2, bcl-2-associated X protein (Bax), IL-1β, IL-6β, TNF-α. Moreover, OGD/R induced the up-regulation of p-p65, p-IκB and p-p38, which were effectively decreased after TPPU pretreat¬ment in comparison with that of the OGD/R group. Furthermore，pyrrolidinedithiocarbamate (PDTC, a selective inhibitor of NF-κB p65) not only alleviated the OGD/R-induced HBMVECs injury and permeability, but also reduced the expression of TNF-α, IL-6, IL-1β, p-p65 and p-IκB, and the protective effect of PDTC was equivalent to that of TPPU. These results indicate that TPPU protects BBB integrity against ischemic injury by multiple protective mechanisms, at least in part, by reducing ROS, inflammation, apoptosis, and suppressing the nuclear factor-κB (NF-κB) and p38 signaling pathways.